Penggunaan Musik Daerah Untuk Meningkatkan Kompetensi Kecepatan Dan Ketepatan Mengetik Mahasiswa - Setiawardani, Maya; Suhaeni, Tintin (Jurnal Riset Bisnis dan Investasi, 2016)
Mastery of keyboarding being part urgent to communicate through the computer, and very important, especially students who study in the field of business. On the other side, individual performance also influenced by the work environment, and music is one form the environment that could effect keyboarding performance. A model that can describe this is the stimulus-responsible model of mehrabian-russell which explains that music can affect the performance of individual writing. Almost all of Indonesia has traditional music. Therefore, research is needed to identify the effects of traditional music to enrich the area of innovation in strategies and techniques of learning keyboarding skills. In this study conducted an experiment on two groups, the treatment groups(traditional music) and control group (without traditional) and questionnaire to strengthen the experimental results. In preliminary tests of typing, both groups had a mean AWPM identical or similar. Furthermore, tests carried one, where the treatment group listened to five kinds of music Java, Sunda, and Bali. The test result and the result of the questionnaire showed that (typing skills shown by the average value of AWPM) will increase significantly used of traditional music as the background. So, the genre of traditional music can be stimulant to improve average performance of AWPM. There are three traditional kinds of music that can improve student typing speed and accuracy significantly, a regional music cublek-cublek suweng, kebiar bali, and oleg tambuliningan, but cublek-cublek suweng is a genre of traditional music that has the best effect. Therefore, the process of learning courses keyboarding skills needs to use instrumental traditional music, especially instrumental music that has a fast and cheerfully tempo.